Ultra Vires without End? The German perspective on the Future of Europe Conference - Schaefer, Jan Philipp (Maastricht 30: A Central European Perspective, 2025)
The paper deals with the German perspective on the FoEC reform process within the framework of the European Union. In this context, an overview is given of the relevant case law of the German Federal Constitutional Court, which is the actual key player in integration policy in the Federal Republic of Germany. The jurisprudence of the Federal Constitutional Court reflects the doctrines developed by German European legal scholarship since the 1950s, which focus on the compatibility of post-nationalsovereignty with the constraints of integration policy. This article introduces the history of German European legal scholarship. Only from this perspective can the German positions on European budgetary sovereignty, the democratic development of the Union and questions of deeper cooperation in climate protection or pandemic management be illuminated. Keywords: democracy, depolitization, functional integrative association, Walter Hallstein, Hans Peter Ipsen, Lisbon decision (FCC), Maastricht decision (FCC), neutralization, the political, Solange I decision (FCC), Solange II decision (FCC), special purpose association